Chemical Pulps for Writing and Printing Papers from Albi ia procera Benth. (White Siris) - Guha, S. R. D.; Prasad, B. D. (Indian Forester, 1961)
Laboratory experiments on production of chemical pulps from Albi ia procera Benth. (white siris) for writing and printing papers by sulphate process are described. The average fibre length of the pulp was 0.90 mm. and the average fibre diameter was 0.021 mm. Easy bleaching pulps in good yields with satisfactory strength properties could be prepared under suitable conditions of digestion. The investigation reported in this paper has shown that Albi ia procera is a promising fibrous raw material for the manufacture of white writing and printing papers. The results of these experiments require to be confirmed by pilot-plant trials.